2012
DOI: 10.1063/1.4761981
|View full text |Cite
|
Sign up to set email alerts
|

Water assisted gate induced temporal surface charge distribution probed by electrostatic force microscopy

Abstract: Articles you may be interested inEffect of surface charge on water film nanoconfined between hydrophilic solid surfacesIn this paper, we present a quantitative method to measure charge density on dielectric layers using electrostatic force microscopy. As opposed to previous reports, our method, which is based on force curve measurements, does not require preliminary knowledge of the tip-sample capacitance and its derivatives. Using this approach, we have been able to quantify lateral and temporal SiO 2 surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…In a recent study, 27 we reported on gate-induced waterassisted surface charge redistribution on dielectric layers. Briefly, the temporal behavior for this phenomenon indeed follows an exponential time dependence which was attributed to charge transport along the oxide surface that acts as a leaky capacitor.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, 27 we reported on gate-induced waterassisted surface charge redistribution on dielectric layers. Briefly, the temporal behavior for this phenomenon indeed follows an exponential time dependence which was attributed to charge transport along the oxide surface that acts as a leaky capacitor.…”
Section: Resultsmentioning
confidence: 99%
“…A similar charge distribution on the surface of silicon oxide under highly humid conditions (not in the solution environment) has been reported in electrical probing techniques and has been attributed to the formation of positive charges in the middle of the metallic electrodes. 30 Note that such an ion-induced PC (IPC) signal along the SWNT axis is pronounced when the ionic strength of the water is very low, e.g., less than $0:5 lM. The ionic strength tends to increase as the carbon dioxide (CO 2 ) from the ambient air dissolves into the solution.…”
mentioning
confidence: 99%
“…[ 90 ] Other researchers also reported that atmospheric moisture and the water molecules in the film could increase the probability of charge injection and accelerate the diffusion of trapped charges. [ 2,46,47,60,78,87,101–105 ] In addition, a higher H 2 O and O 2 concentration may be one of the important factors in improving the charge trap rate. [ 66 ]…”
Section: The Properties Of Trapping Charges For Different Materials Bmentioning
confidence: 99%
“…[ 16,40,42,44,46,47,55,57,60,69,70,79,87,101–103,106,112,117–121 ] Some groups have reported that charge injection is influenced by the hydrophilicity of films and the atmospheric moisture. [ 46,47,60,101–103 ] The effects of the injection time, [ 44,46,79,119 ] injection bias, [ 40,44,79,119 ] and the duration of the applied field [ 113 ] on the charge trapping processes have also been widely investigated. Maedler and Graaf investigated the relationship of trapped charges and the injection time and found that the quantity of trapped charges is nonlinearly dependent on the injection times.…”
Section: The Mechanism Of Injection and Decaymentioning
confidence: 99%